Prevotella histicola, A Human Gut Commensal, Is as Potent as COPAXONE® in an Animal Model of Multiple Sclerosis - Shahi, Shailesh K.; Freedman, Samantha N.; Murra, Alexandra C.; Zarei, Kasra; Sompallae, Ramakrishna; Gibson-Corley, Katherine N.; Karandikar, Nitin J.; Murray, Joseph A.; Mangalam, Ashutosh K. (Frontiers in Immunology, 2019)
Multiple sclerosis (MS) is a demyelinating disease of the central nervous system. We and others have shown that there is enrichment of some or depletion of other gut bacteria in MS patients compared to healthy controls (HC), suggesting the gut microbiota plays an important role in disease pathogenesis. Thus, specific gut bacteria that are lower in abundance in MS patients could be used as a potential treatment option for this disease. In particular, we and others have shown that MS patients have a lower abundance of Prevotella compared to HC, whereas the abundance of Prevotella is increased in patients that receive disease-modifying therapies such as Copaxone® (Glatiramer acetate-GA). This inverse correlation between the severity of MS disease and the abundance of Prevotella suggests its potential for use as a therapeutic option to treat MS. Notably we have previously identified a specific strain, Prevotella histicola (P. histicola), that suppresses disease in the animal model of MS, experimental autoimmune encephalomyelitis (EAE) compared with sham treatment. In the present study we analyzed whether the disease suppressing effects of P. histicola synergize with those of the disease-modifying drug Copaxone® to more effectively suppress disease compared to either treatment alone an affect Copaxone did not have. Treatment with P. histicola was as effective in suppressing disease as treatment with Copaxone®, whereas the combination of P. histicola plus Copaxone® was not more effective than either individual treatment. P. histicola-treated mice had an increased frequency and number of CD4+FoxP3+ regulatory T cells and a decreased frequency of pro-inflammatory IFNγ- and IL17-producing CD4 T cells in the CNS, suggesting P. histicola suppresses disease by boosting anti-inflammatory immune responses and inhibiting pro-inflammatory immune responses. In conclusion, our study indicates that the human gut commensal P. histicola can suppress disease as efficiently as Copaxone® and may provide an alternative treatment option for MS patients.